Faktor-Faktor yang Mempengaruhi Minat Siswa Kelas IX SMP untuk Lanjut Studi ke SMK - Nur Rizkiyah (Peneliti.net, 2020)
The purpose of this study was to determine the factors that influence students in choosing SMK, after they finish their junior high school studies. The method used was a qualitative method. The sample used was 35 students. The results showed that internal factors had the most dominant factors, while emotional factors were not dominant factors. BK teachers were expected to be able to assist students in choosing the school they will choose. Parents, could provide encouragement, so that students could choose according to their own decisions. The most dominant factors that influenced students' interest in continuing studies at vocational schools were internal encouragement, while the lowest dominant factor was social factors